2017
DOI: 10.24042/klm.v10i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Abdurrahman Wahid: Universalisme Islam dan Toleransi

Abstract: Abstrak Artikel ini membahas pemikiran Abdurrahman Wahid tentang universalisme Islam dan toleransi. Pemikiran tentang universalisme Islam dan toleransi penting dibahas di tengah menguatnya gerakan Islam radikal di Indonesia. Eksistensi dan aksi kelompok A. PendahuluanIndonesia merupakan negara yang memiliki tingkat pluralitas yang tinggi. Perbedaan berbagai aspek-agama, budaya, suku, ras, golongan, dan berbagai bentuk keanekaragaman yang lainnyamenjadi bagian yang tidak terpisah dari kehidupan. Perbedaan terse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
0
7
0
7
Order By: Relevance
“…This is based on Al-Qur'an, as the main source of Islamic teachings, in surah Al-Baqoroh verse 222 and Al-Mudatsir verses 4-5. Likewise, tolerance is very important to grow in students because any religion teaches to spread love, and Islam is a user-friendly and very tolerant religion (Fadzil, 2011;;Misrawi, 2010;Naim, 2016;Suryan, 2017;Yasir, 2014).…”
Section: Pre-action Analysismentioning
confidence: 99%
“…This is based on Al-Qur'an, as the main source of Islamic teachings, in surah Al-Baqoroh verse 222 and Al-Mudatsir verses 4-5. Likewise, tolerance is very important to grow in students because any religion teaches to spread love, and Islam is a user-friendly and very tolerant religion (Fadzil, 2011;;Misrawi, 2010;Naim, 2016;Suryan, 2017;Yasir, 2014).…”
Section: Pre-action Analysismentioning
confidence: 99%
“…Percaya diri adalah sesuatu yang tidak ternilai. Dengan memiliki percaya diri, seseorang dapat melakukan apa pun dengan keyakinan bahwa itu akan berhasil, apabila ternyata gagal, seseorang tidak lantas putus asa, tetapi tetap masih mempunyai semangat, tetap bersikap realistis, dan kemudian dengan mantap mencoba lagi [39]. Rasa percaya diri pada siswa ini harus dipertahankan sebagai mana, rasa ketidaktakutan yang ada pada diri siswa tersebut harus dilatih dalam pendidikan.…”
Section: Ketidaktahuanunclassified
“…In addition, exclusive religious understanding will have an impact on prolonged and complicated intolerance conflicts. [36] Intolerance itself is a form of behavior that is not characterized [37], the difference can also trigger intolerant conflict. [38] So it can be concluded that conflict of intolerance is a split due to a lack of respect for differences in opinions, cultures, and religions that often lead to misunderstandings.…”
Section: B Intolerant Conflict Among Youth Generationmentioning
confidence: 99%
“…The term tolerance in Latin is called tolerare, it means restraint, letting people think, be broad-minded to the views of others. Tolerance does not mean justifying the views or streams that are left but recognizes the freedom and human rights of the adherents [71].…”
Section: Role Of Families In Internalizing Multi-religion Tolerancmentioning
confidence: 99%